STUDIES ON MORPHOLOGICAL FEATURE OF ANTHERAEA ASSAMA W.W. (LEPIDOPTERA : SATURNIDAE) - GHORAI, R.; CHAUDHURI, N.; SENAPATI, S.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2010)
Morphological study of muga silk moth Antheraea assama WW. showed that the adult female of muga silk moth Antheraea assama was larger than the male counter part in respect to the size of body, leg, wing and antenna. Twenty one (21) different types of scales have been identified over the body surface.